Reggio Emilia Sistemi ve Mekânsal Kurguya Etkisi - Özcan, Uğur; Cestel, Tuğba (Prchitect, 2020)
Bir toplumun geleceğinin yapı taşlarından olan eğitim sistemi, genç nüfusun zihinsel, sosyal ve duygusal gelişimleri üzerinde etkili olan eğitim yapıları ile sağlanır. Zihinsel gelişimin en önemli dönemi 0-6 yaş aralığı olduğu belirlenmiştir ve bilinçsiz öğrenmenin bilinçli öğrenme seviyesine geçtiği bu dönemi tüm yönleriyle destekleyecek sosyal ve fiziksel çevre, okul öncesi ile başlayıp sonraki yıllarda da devamı olan eğitim kurumlan tarafından sağlanmalıdır (Gökmen, 2013). İnsanoğlunun gelişiminde önemli bir rolü olan eğitimin kalitesi, uygulanan eğitim yöntemine bağlı olduğu kadar, doğru olarak kurgulanması ve etkin bir şekilde hayata geçirilmesini sağlayacak mekanların tasarlanmasına bağlıdır. Günümüzde birçok eğitim yaklaşımı çevre faktörü üzerinde önemle durmaktadır. Çocukların gelişimi için kullanılmaya devam eden alternatif eğitim sistemlerinden Reggio Emilia yaklaşımının mekansal kurguya etkisini, farklı kültür ve coğrafi özelliklere sahip bölgelerde bulunan örnekleri ile ele alabilmek ve değerlendirmek mümkündür.

The continuation of the social and physical environment that will support ali aspects of the development of school-age children is carried out with the design of educational structures. Education Systems play an important role in the proper design and effective implementation of these structures. Dewey, Montessori, Waldorf and Reggio Emilia approaches are among the leading altemative education Systems in the world. The Reggio Emilia approach, which is the subject of this article, is an educational system thât allows the learner to be transformed and developed by the learner and emphasizes the role of the physical environment placed in the position of a third teacher. In the forefront of art activities, the focus is on how the products produced individually or as a group are formed rather than what they are. Reggio, which does not include Standard accreditation processes and certified teacher programs is an education system that is not formal model, nurtured and adaptable to the culture of the place. In the educational institutions designed with this method, the creation of common and flexible spaces by arranging the interior and exterior spâces together takes the first place in planning. In the structures formed from functionality rather than form, the relationship betvveen settlement, bearing system, façade and garden is examined by considering the location. Classes, workshops and in-school circulation areas are supportive space equipment in the student-teacher relationship with material and color selection. Within this framework, where each leaming environment is thought to be contextually and culturally peculiar to the place, inthe design of school buildings located in different regions and climatic conditions of the worldand providing education with the Reggio Emilia system, the reflections of the approaches on spatial fiction and then the development of individuals are examined in this study.
Reggio Emilia System and Effects on Spatial Fiction